Numerical analysis of elastic wave mode conversion on discontinuities. (1st May 2019) - Wandowski, T.; Kudela, P.; Ostachowicz, W.M.
Highlights: Detailed numerical analysis of S0/A0 mode conversion phenomenon on the delamination based on spectral element method. Analysis of wavefield (including S0/A0 mode conversion) distribution through the thickness in the delaminated region. Implementation of the model for impact damage. Full wavefield measurements and numerical results show good agreement. Abstract: In this paper results of numerical analysis of S0/A0 elastic wave mode conversion at discontinuities in glass fibre reinforced polymer (GFRP) plates are presented. Analysis of S0/A0 mode conversion effect at Teflon inserts simulating delamination (circular Teflon inserts located at a different depth, Teflon inserts with different shapes at the same depth) and impact damage with energies 5 J, 10 J and 15 J is conducted. Numerical analysis is based on spectral element method (SEM) in the time domain. Numerical model includes a composite plate, a piezoelectric transducer and bonding layer for transducer and damage. Numerical model takes also into account the influence of material damping. Numerical results are compared with experimental results based on full wavefield measurements using scanning laser Doppler vibrometry (SLDV). It is shown that based on effects of S0/A0 mode conversion it is possible to detect the damage and determine its shape and size.